If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x + 20) = 84 Reorder the terms: x(20 + x) = 84 (20 * x + x * x) = 84 (20x + x2) = 84 Solving 20x + x2 = 84 Solving for variable 'x'. Reorder the terms: -84 + 20x + x2 = 84 + -84 Combine like terms: 84 + -84 = 0 -84 + 20x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '84' to each side of the equation. -84 + 20x + 84 + x2 = 0 + 84 Reorder the terms: -84 + 84 + 20x + x2 = 0 + 84 Combine like terms: -84 + 84 = 0 0 + 20x + x2 = 0 + 84 20x + x2 = 0 + 84 Combine like terms: 0 + 84 = 84 20x + x2 = 84 The x term is 20x. Take half its coefficient (10). Square it (100) and add it to both sides. Add '100' to each side of the equation. 20x + 100 + x2 = 84 + 100 Reorder the terms: 100 + 20x + x2 = 84 + 100 Combine like terms: 84 + 100 = 184 100 + 20x + x2 = 184 Factor a perfect square on the left side: (x + 10)(x + 10) = 184 Calculate the square root of the right side: 13.564659966 Break this problem into two subproblems by setting (x + 10) equal to 13.564659966 and -13.564659966.Subproblem 1
x + 10 = 13.564659966 Simplifying x + 10 = 13.564659966 Reorder the terms: 10 + x = 13.564659966 Solving 10 + x = 13.564659966 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = 13.564659966 + -10 Combine like terms: 10 + -10 = 0 0 + x = 13.564659966 + -10 x = 13.564659966 + -10 Combine like terms: 13.564659966 + -10 = 3.564659966 x = 3.564659966 Simplifying x = 3.564659966Subproblem 2
x + 10 = -13.564659966 Simplifying x + 10 = -13.564659966 Reorder the terms: 10 + x = -13.564659966 Solving 10 + x = -13.564659966 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + x = -13.564659966 + -10 Combine like terms: 10 + -10 = 0 0 + x = -13.564659966 + -10 x = -13.564659966 + -10 Combine like terms: -13.564659966 + -10 = -23.564659966 x = -23.564659966 Simplifying x = -23.564659966Solution
The solution to the problem is based on the solutions from the subproblems. x = {3.564659966, -23.564659966}
| 4x^2-4-8=0 | | k-2+4k=8 | | 7k^2+9k=0 | | 3x+4-5x=9+8x | | 10x^2-17x=0 | | 12a+1b=50 | | 2y+2=3y-9 | | 7x^2-31x-20=0 | | 4a-6b=96 | | 6(0.3333333333+-0.1666666667b)=3-b | | 6x^2+3x+24=3 | | 4a+6b=96 | | -1+3=x+2 | | x+3(x-1)=6-4(2x+3) | | x+0.03x=208 | | 3(2n-1)=3(n+3) | | 4y^2=18x-2 | | m^2-5m=6 | | 18=d-6 | | 10-4s+2s-3= | | 5y+3x=15 | | 9h^2+144x+1=0 | | 3x-23=1 | | 3x+10=8x+5 | | 7-(2x-1)=10 | | m^2-9m+8=0 | | m^2-9+8=0 | | 5j=15 | | 1.66j=15 | | 1.67j=15 | | 1.3a=1.1a | | x^2+16x-9=0 |